Seamus Heaney's "Failed" Elegy and the Nonhuman Subject: A Reading of "Widgeon". Issue 1 (16th June 2022) - Shi, Huiwen
Abstract: In addition to linguistic and cultural mediations, Seamus Heaney's work also situates itself between life and death. Often his poetry is perceived as elegiac, with the loss of rural life and agricultural crafts, the end of innocence and childhood, memories of late family members, and the deaths in the conflicts in Northern Ireland, all becoming subjects of his mourning. This paper examines Heaney's unique treatment of a nonhuman death in "Widgeon", one of his shortest and least examined poems. In this poem, the dead body is exposed, and its voice takes over the human elegiac cry. Importantly, the poem raises the ethical question of the living misreading the dead in elegy. Failing to reach consolation, it arrives at an unexpected irresolution, unresting the dead as well as arresting the living.